Boosting Ethanol Productivity of Zymomonas mobilis 8b in Enzymatic Hydrolysate of Dilute Acid and Ammonia Pretreated Corn Stover Through Medium Optimization, High Cell Density Fermentation and Cell Recycling - Li, Ying; Zhai, Rui; Jiang, Xiaoxiao; Chen, Xiangxue; Yuan, Xinchuan; Liu, Zhihua; Jin, Mingjie (Frontiers in Microbiology, 2019)
The presence of toxic degradation products in lignocellulosic hydrolysate typically reduced fermentation rates and xylose consumption rate, resulting in a decreased ethanol productivity. In the present study, Zymomonas mobilis 8b was investigated for high cell density fermentation with cell recycling to improve the ethanol productivity in lignocellulosic hydrolysate. The fermentation performances of Z. mobilis 8b at various conditions were first studied in yeast extract-tryptone medium. It was found that nutrient level was essential for glucose and xylose co-fermentation by Z. mobilis 8b and high cell density fermentation with cell recycling worked well in yeast extract-tryptone medium for 6 rounds fermentation. Z. mobilis 8b was then studied in enzymatic hydrolysates derived from dilute acid (DA) pretreated corn stover (CS) and ammonia pretreated CS for high cell density fermentation with cell recycling. Ethanol productivity obtained was around three times higher compared to traditional fermentation. Ethanol titer and metabolic yield were also enhanced with high cell density fermentation. Z. mobilis 8b cells showed high recyclability in ammonia pretreated CS hydrolysate.